2017
DOI: 10.1123/ijspp.2016-0783
|View full text |Cite
|
Sign up to set email alerts
|

Updated Review of the Applied Physiology of American College Football: Physical Demands, Strength and Conditioning, Nutrition, and Injury Characteristics of America’s Favorite Game

Abstract: While there are various avenues for performance improvement in college American football (AF), there is no comprehensive evaluation of the collective array of resources around performance, physical conditioning, and injury and training/game characteristics to guide future research and inform practitioners. Accordingly, the aim of the present review was to provide a current examination of these areas in college AF. Recent studies show that there is a wide range of body compositions and strength characteristics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
27
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 79 publications
(110 reference statements)
4
27
0
1
Order By: Relevance
“…Using 2 seasons worth of data together did not bring forth clear representative clusters that resembled traditional "bigs, big-skills, and skills" groupings (Pincivero & Bompa, 1997) like the data from the individual seasons. A clear differentiation still exists between the group of WRs and DBs and the group of OLs and DLs as noted in previous studies (Fullagar et al, 2017), but the other positions do not seem to split up as uniformly. Using 4 clusters aids this dilemma by creating groups that can be loosely identified in Table 7 as "bigs" (cluster 2), "big-skills" (cluster 1), and "skills" (clusters 3 and 4).…”
Section: Seasons 1 Andsupporting
confidence: 68%
See 1 more Smart Citation
“…Using 2 seasons worth of data together did not bring forth clear representative clusters that resembled traditional "bigs, big-skills, and skills" groupings (Pincivero & Bompa, 1997) like the data from the individual seasons. A clear differentiation still exists between the group of WRs and DBs and the group of OLs and DLs as noted in previous studies (Fullagar et al, 2017), but the other positions do not seem to split up as uniformly. Using 4 clusters aids this dilemma by creating groups that can be loosely identified in Table 7 as "bigs" (cluster 2), "big-skills" (cluster 1), and "skills" (clusters 3 and 4).…”
Section: Seasons 1 Andsupporting
confidence: 68%
“…The playstyle of the individual at these positions undoubtedly has a large effect on how they are clustered. This brings clarity to the idea of how different playstyles can affect the demands of positions (Fullagar, McCunn, & Murray, 2017), which is evidence that this tool could aid in The two resultant "skills" clusters were interesting as it suggests that the technique differentiated "covering," a job performed by DBs and sometimes LBs, and "route-running," a job performed by WRs and sometimes TEs, before it differentiated the demands of RBs and DLs in the "big-skills" group of k=3 displayed in Figure 3. This differentiation does not emerge until the dataset is clustered using 6 centers.…”
Section: Seasonmentioning
confidence: 99%
“…The laboratory assays indicated normal salivary parameters in those participants with NCCLs; therefore, these lesions seem related to excessive mechanical stress and not to erosive factors such as acidic beverages or brushing immediately after meals. Fullagar et al reported that footballers possess limited nutrition and hydration practices [ 42 ]. The level of cortisol of all participants was found normal.…”
Section: Discussionmentioning
confidence: 99%
“…Among typical non-contact injuries, anterior cruciate ligament (ACL) ruptures (1.00 injury/1000 athlete-exposures) 6 and hamstring strains (1.67 injury/1000 athlete-exposures) 8 have been associated with some athletes' intrinsic features, such as the muscle strength imbalance between hamstring and quadriceps muscles (e.g., hamstring-toquadriceps ratio) 9,10 and strength imbalance between preferred and nonpreferred limbs (e.g., bilateral asymmetry) 10 . Thus, AF teams from USA have increasingly invested in isokinetic dynamometry tests 3 .…”
Section: Introductionmentioning
confidence: 99%